Impact of Taxanes, Endocrine Therapy, and Deleterious Germline BRCA Mutations on Anti-müllerian Hormone Levels in Early Breast Cancer Patients Treated With Anthracycline- and Cyclophosphamide-Based Chemotherapy - Lambertini, Matteo; Olympios, Nathalie; Lequesne, Justine; Calbrix, Céline; Fontanilles, Maxime; Loeb, Agnès; Leheurteur, Marianne; Demeestere, Isabelle; Di Fiore, Frédéric; Perdrix, Anne; Clatot, Florian (Frontiers in Oncology, 2019)
Background Limited evidence exists on the impact of adding a taxane, using endocrine therapy and carrying a deleterious germline BRCA mutation on ovarian reserve measured by anti-müllerian hormone (AMH) levels of young breast cancer patients receiving (neo)adjuvant cyclophosphamide- and anthracycline-based chemotherapy. Methods This is a biomarker analysis including young (≤40 years) early breast cancer patients with known germline BRCA mutational status and available prospectively collected frozen plasma samples before and after chemotherapy. Chemotherapy consisted of either six cycles of FEC (5 fluorouracil 500 mg/m2, epirubicin 100 mg/m2, cyclophosphamide 500 mg/m2) or three cycles of FEC followed by three cycles of docetaxel (D, 100 mg/m2). Endocrine therapy consisted of tamoxifen (±GnRH agonists). AMH levels at baseline, one and three years after diagnosis were compared according to type of chemotherapy (FEC only vs. FEC-D), use of endocrine therapy (yes vs. no) and deleterious germline BRCA mutations (mutated vs. negative). Results Out of 148 included patients, 127 (86%) received D following FEC chemotherapy, 90 (61%) underwent endocrine therapy and 35 (24%) had deleterious germline BRCA mutations. In the whole cohort, AMH levels drastically dropped one year after diagnosis (p<0.0001) with a slight but significant recovery at three years (p<0.0001). One year after diagnosis, patients treated with FEC only had higher median AMH levels than those who received FEC-D (0.22 μg/L vs. 0.04 μg/L, p=0.0006); no difference was observed at three years (0.06 μg/L and 0.18 μg/L, p=0.47). Patients under endocrine therapy had significantly higher AMH levels than those who did not receive this treatment one year after diagnosis (0.12 μg/L vs. 0.02 μg/L; p=0.008), with no difference at three years (0.11 μg/L and 0.20 μg/L, p=0.22). AMH levels were similar between BRCA-mutated and BRCA-negative patients at baseline (1.94 μg/L vs. 1.66 μg/L, p=0.53), one year (0.09 μg/L vs. 0.06 μg/L, p=0.39) and three years (0.25 μg/L vs. 0.16 μg/L; p=0.43) after diagnosis. Conclusions In breast cancer patients receiving FEC chemotherapy, adding docetaxel appeared to negatively impact on their ovarian reserve in the short-term; no further detrimental effect was observed for endocrine therapy use and presence of a deleterious germline BRCA mutation.